OPTIMALISASI PROGRAM RUTINAN HUBUNGAN MASYARAKAT PADA PT INDONESIA POWER SURALAYA POWER GENERATION UNIT KOTA CILEGON - Titi Stiawati; Iis Nur Annisa (LPPM STIA Banten, 2022)
The research focus is on the routine program of the public relations division of PT Indonesia Power Suralaya PGU. A routine program is an activity that is carried out regularly either on a daily, weekly or monthly basis. PT Indonesia Power's public relations division has several internal and external routine programs, which have been well implemented. However, in its implementation there are still some obstacles such as differences in information obtained between public relations division employees. The method used is descriptive qualitative. The purpose of this research is to find out what must be optimized in routine programs so that the constraints encountered can be overcome properly. The theory used is the performance theory of Agus Dwiyanto (2006) consisting of five variables, however the researcher chose to use only three indicators, namely responsiveness, responsibility and accountability. The results of this study indicate that the implementation of routine programs in the public relations division is good, but there are some things that are not optimal. The responsiveness variable has not been maximized because there is still misinformation between public relations division employees so that internal communication needs to be improved. The responsibility variable is good because the awareness of employees to work together in other tasks is high. While the accountability variable is good because the service provided by employees is quite good, namely being able to provide satisfaction for employees of other divisions and external parties of PT Indonesia Power Suralaya PGU.